Preserving esthetics, occlusion and occlusal vertical dimension in a patient with fixed prostheses seeking dental implant treatment - Abdulaziz Al Baker; Syed Rashid Habib; Mohammad D. Al Amri (Elsevier, 2016)
The preservation of esthetics and occlusal vertical dimension is critical in patients with existing full-arch tooth-retained fixed prostheses. This clinical report describes the provision of a maxillary immediate complete denture in a patient with a maxillary full-arch fixed dental prosthesis over nonviable teeth. The existing fixed dental prosthesis was used in the fabrication of the maxillary immediate complete denture to preserve esthetics. The technique involved recording and preservation of the occlusal vertical dimension and occlusion of the existing prosthesis. The technique is simple, quick, cost-effective and less challenging clinically and technically. Keywords: Esthetics, Occlusal vertical dimension, Dental implants, Fixed partial dentures, Occlusion, Immediate dentures